Flow Cytometric Ploidy Analysis in Acute Lymphoblastic Leukemia and Plasma Cell Myeloma - Bommannan, Karthik (Indian Journal of Medical and Paediatric Oncology, 2023)
Identification of underlying cytogenetic (CG) aberrancies plays a significant role in risk stratification of hematological malignancies. These abnormalities can be due to aberrancies that affect the number or structure of chromosomes. Numerical chromosomal abnormalities are called aneuploidies, which result from either gain or loss of whole chromosomes. Ploidy assessment by CG is a laborious and less sensitive technique. With the aid of fluorescent nucleic acid binding dyes, the total DNA content and different phases of the cell cycle specific to any population of interest can be deciphered and analyzed by flow cytometry (FCM). DNA index (DI), a parameter derived by FCM DNA analysis, is equivalent to conventional CG-based ploidy assessment. In this study, the technical aspects and implications of FCM DNA assessment among patients diagnosed with acute lymphoblastic leukemia and plasma cell myeloma are discussed.
Keywords: ploidy; flow cytometry; DNA Index; S-phase fraction